Author's reply - Kirkil, Cüneyt (Turkish Society of Gastroenterology, 2015)
[Abstract Not Available]
Keywords: Anti-Bacterial Agents; Appendicitis; Female; Humans; Male; antiinfective agent; acute appendicitis; appendectomy; conservative treatment; cost benefit analysis; follow up; hospital charge; hospital cost; human; Letter; noncomplicated acute appendicitis; treatment outcome; appendicitis; female; male